Informatywno prognostyczna wskalników koordynacyjnych zdolnosci motorycznych (KZM) w ocenie perspektywicznosci wyselekcjonowanych pilkarzy noznych w wieku 16-19 lat. Dane - Liakh, V.; Zmuda, W.; Wirkowski, Z. (Human Movement, 2001)
The aim of this paper was to evaluate the prognostic value of 23 indices related to 7 coordination motor abilities (tab. 1) in young, highly qualified soccer players. This research included 26 players aged between 16 and 19 from the School of Sport Championships in Zabrze. The measurements were taken three times, year by year (in 1998, 1999, 2000) in 16-17, 17-18 and 18-19 players' age groups. The prognostic coefficients of particular indeces and the whole battery of tests have been evaluated by Spearman's correlation. The outcome is presented in table 1. The highest prognostic value is characteristic of the indices of motor adjustment (no. 13-18), movement combining (no. 19-20), rhythm (no. 1-6) as well as dynamic (no. 9) and static balance (no. 7). A slightly lower prognostic value was observed in the case of speed of reaction (no. 21). The smallest prognostic value occurred in the case of indices of kinesthetic differentiation (no. 10-12) and space orientation (no. 22-23) (between 1 and 2 measurements). It has been disclosed that the most prognostically valuable indices of football playing abilities are the evaluations of coordinational preparations carried out on the ground of the whole battery of motoric tests. The correlation coefficient between this kind of evaluations is always high and equals above 0,80 (table 1). The particular CMA indices as well as the whole battery of tests may be used in the process of specialised selection and during prognosis development.